Induced Innovation and International Environmental Agreements: Evidence from the Ozone Regime - Eugenie Dugoua (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper revisits one of the rare success stories in global environmental cooperation: the Montreal Protocol and the phase-out of ozone-depleting substances. I show that the protocol increased science and innovation on alternatives to ozone-depleting substances, and argue that agreements can indeed be useful to solving global public goods problems. This contrasts with game-theoretical predictions that agreements occur only when costs to the players are low, and with the often-heard narrative that substitutes were readily available. I reconcile theory and empirics by discussing the role of induced innovation in models of environmental agreements.
Keywords: O30; Q55; 330; induced innovation; directed technological change; green innovation